Future of the transdermal drug delivery market – have we barely touched the surface?. (2nd April 2016) - Watkinson, Adam C.; Kearney, Mary-Carmel; Quinn, Helen L.; Courtenay, Aaron J.; Donnelly, Ryan F.
ABSTRACT: Introduction : Transdermal drug delivery is the movement of drugs across the skin for absorption into the systemic circulation. Transfer of the drug can occur via passive or active means; passive transdermal products do not disrupt the stratum corneum to facilitate delivery whereas active technologies do. Due to the very specific physicochemical properties necessary for successful passive transdermal drug delivery, this sector of the pharmaceutical industry is relatively small. There are many well-documented benefits of this delivery route however, and as a result there is great interest in increasing the number of therapeutic substances that can be delivered transdermally. Areas Covered : This review discusses the various transdermal products that are currently/have been marketed, and the paths that led to their success, or lack of. Both passive and active transdermal technologies are considered with the advantages and limitations of each highlighted. In addition to marketed products, technologies that are in the investigative stages by various pharmaceutical companies are reviewed. Expert Opinion : Passive transdermal drug delivery has made limited progress in recent years, however with the ongoing intense research into active technologies, there is great potential for growth within the transdermal delivery market. A number of active technologies have already been translated into marketed products, with other platforms including microneedles, rapidly progressing towards commercialisation.